Contextual teaching and learning-based functional academic teaching materials for the teachers specialized in educating the students with visual impairment - Sayidatul Maslahah; Ishartiwi Ishartiwi; Mumpuniarti Mumpuniarti; Yeni Irma Normawati (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
The objective of the study is to develop the Contextual Teaching and Learning (CTL)-based functional academic teaching materials for the teachers specialized in educating the students with different visual ability. The method that has been adopted within the conduct of the study is Research and Development (RD) with reference to the Borg amp; Gall Model by means of experiment limitation. The study itself has been conducted in the Yaketunis Special School Type A, which has been the school for the students with different visual ability in Yogyakarta. The results of the study, which cover the stages of needs analysis in the given special school, show that up to date there has not been any written systematic functional academic learning. In addition, the results of the study also show that the teachers still have been dealing with the efforts of teaching the functional academic because the curriculum has been the modification of the regular curriculum. Therefore, the teachers demand the functional academic teaching materials for the students with different visual ability. Based on the results of the expert judgment by the media expert, the material expert and the experiment with the teacher, the functional academic teaching materials have been declared good and fit for implementation in the school. Then, the aspects that have been assessed within the expert judgment are namely material/content, presentation, linguistic and graphic. Furthermore, the score by 3.65 from the media expert and the score 3.80 from the material expert imply that the product in the form of functional academic teaching materials have been very fit and good for implementation by the teachers specialized in teaching the students with different visual ability. In addition, the response within the experiment stage also show that the mean score has been 3.70; as a result, the product in the form of Contextual Teaching and Learning (CTL)-based functional academic teaching materials have good for implementation. In other words, it might be concluded that the Contextual Teaching and Learning (CTL)-based functional academic teaching materials have been feasible for implementation for the teachers specialized in educating the students with different visual ability in the terms of functional reading, writing and counting activities.